2016
DOI: 10.1007/s00606-016-1288-4
|View full text |Cite
|
Sign up to set email alerts
|

Insights into developmental processes in anthers, ovaries, and ovules of Taraxacum belorussicum (Asteraceae-Cichorioideae) using DIC optics

Abstract: This study represents the first report on the embryological characteristics of triploid male-sterile dandelion Taraxacum belorussicum (section Palustria) from Poland. While this taxon is considered to be a male-sterile species, we found that the investigated individuals produced pollen. Irregular tetrads, triads and diads with microspores of unequal size were observed in the pollen loculi as a result of disturbed meiotic division, while anthers' tapetum did not show structural disorders. Possible reasons for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…A liquefaction (or gelatinization) of the integument cells adjacent to endothelium was also observed in other sexual and apomictic Pilosella species (Koltunow et al 1998 ; Płachno et al 2017 ). Similarly, the peri-endothelial zone occurrence was characteristic of the ovules of Taraxacum and Chondrilla species (Cooper and Brink 1949 ; Janas et al 2016 ; Musiał and Kościńska-Pająk 2013 ; Musiał et al 2013 ; Płachno et al 2016 ). The structural changes recorded in this region of the integument were accompanied by the accumulation of carbohydrate-rich material that can potentially be the source of nutrients for the developing female gametophyte and embryo (Cooper and Brink 1949 ; Koltunow et al 1998 ; Musiał and Kościńska-Pająk 2013 ; Musiał et al 2013 ; Płachno et al 2016 , 2017 ).…”
Section: Discussionmentioning
confidence: 95%
“…A liquefaction (or gelatinization) of the integument cells adjacent to endothelium was also observed in other sexual and apomictic Pilosella species (Koltunow et al 1998 ; Płachno et al 2017 ). Similarly, the peri-endothelial zone occurrence was characteristic of the ovules of Taraxacum and Chondrilla species (Cooper and Brink 1949 ; Janas et al 2016 ; Musiał and Kościńska-Pająk 2013 ; Musiał et al 2013 ; Płachno et al 2016 ). The structural changes recorded in this region of the integument were accompanied by the accumulation of carbohydrate-rich material that can potentially be the source of nutrients for the developing female gametophyte and embryo (Cooper and Brink 1949 ; Koltunow et al 1998 ; Musiał and Kościńska-Pająk 2013 ; Musiał et al 2013 ; Płachno et al 2016 , 2017 ).…”
Section: Discussionmentioning
confidence: 95%
“…Existing world literature devoted to representatives of the genus Taraxacum is rather poor and mostly focused on their therapeutic properties (Ahmad et al 2000;Chunga et al 2018), developmental and embryological processes (Janas et al 2016), and their application in in vitro culture conditions (Ermayanti and Martin 2011;Tuleja et al 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…T. belorussicum is an interesting obligatory apomictic species (Rodkiewicz et al 1996) and was the object of rare embryological analysis (Małecka 1965(Małecka , 1982Janas et al 2016). Preliminary studies of in vitro plant cultures (Tuleja et al 2014a) revealed direct organogenesis without forming callus, as well as slight somatic embryogenesis on explants from immature parthenogenetic embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B; Table 1) has been characterized in detail in some apomictic Taraxacum spp. (van Baarlen et al, 2000;Musiał et al, 2013;Janas et al, 2016) and Chondrilla spp. (Musiał and Kościńska-Pająk, 2017;.…”
Section: Cytological Characterization Of Diplosporymentioning
confidence: 99%